'A Very Transcendental Power': Denaturalisation and the Liberalisation of Citizenship in the United Kingdom. (11th October 2012) - Gibney, Matthew J.
<x xml:space="preserve">Abstract</x> The right to strip citizenship from (denaturalise) those deemed disloyal or dangerous is a significant but largely unexamined power held by some liberal states. Since 2002, the British government has, in response to concerns about terrorism and value of citizenship, expanded its power to denaturalise certain categories of citizens, including those born in the UK. This development seems odd in the light of academic literature that has described a recent trend in Europe towards the increasing 'liberalisation' of citizenship. Writing on the subject of citizenship acquisition, scholars have pointed to a range of changes that curtail the state's ability to withhold citizenship from resident non‐citizens. In this article, I draw upon parliamentary debates, archived documents, government reports and secondary literature, to chart the historical development of denaturalisation power in the UK and consider the extent to which it has been shaped by liberal principles. This history indicates that denaturalisation had indeed undergone a process of liberalisation before the Labour government partly reversed its direction after 2002. Yet it also shows that liberal principles, far from simply curtailing the state's powers to strip citizenship, have been deeply implicated in recent and historical attempts to expand denaturalisation power by British governments.